Effects of Balanced Ultrafiltration During Extracorporeal Circulation for Children with Congenital Heart Disease on Postoperative Serum Inflammatory Response. (2nd September 2020) - Chen, Feng; You, Yunpeng; Ding, Peicheng; Wu, Kaihong; Mo, Xuming
Abstract: Objectives: We studied inflammatory marker changes with ultrafiltration extracorporeal techniques and compared these levels to those occurring during conventional techniques. Methods: Seventy-four children undergoing extracorporeal circulation during congenital heart surgery were divided into two groups—conventional (control) and balanced ultrafiltrations (study). Serum interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and soluble intercellular adhesion molecule-1 (sICAM-1), static lung compliance (Cstat), alveolar-arterial oxygen partial pressure difference (A-aDO2), and oxygenation index (OI) were measured. Results: Thirty minutes after extracorporeal circulation (T1), IL-6 and TNF-α levels significantly increased ( p < .05), which plummeted 3 h after surgery (T2). The levels in the study group were lower ( p < .05). sICAM-1 levels at T1 and T2 significantly exceeded those at T0, and study group had lower levels ( p < .05). At T1, Cstat and OI dropped ( p < .05), which increased at T2 ( p < .05), and study group had less decreases ( p < .05). A-aDO2 at T1 surpassed that before intervention ( p < .05), and study group had less increase ( p < .05). Conclusion: Balanced ultrafiltration exerts protective effects on children with congenital heart disease undergoing extracorporeal circulation.